(untitled) (Indian Journal of Public Health Research & Development, 2020)
Almost everyone has trouble sleeping once in a while, but if occasional episodes of sleep escalate into an unhealthy night time routine, and it will hamper the productivity and sap the patients quality of life1. Objective: Of this pilot study was to compare the quality of sleep among patients with and without diabetes. Methodology: Quantitative approach with a descriptive design was used. A non-probability convenience sampling technique was used to select samples in this study. A semi-structured questionnaire prepared by the investigator was used to collect the socio-demographic and clinical data from the subjects. A standardized Pittsburgh Sleep Quality Index tool was used to compare the sleep quality among 37 diabetic and 37 nondiabetic subjects. Results: The study findings shows that in both diabetic (DM) and non-diabetic (NDM) subjects majority of the subjects 75.7% and 43.2% respectively were of the age group of 56-65 years. In both the groups majority were male (DM-24 and NDM – 27). The results also showed that among the groups most of the subjects were had high school education, were employed,and were married and had a monthly income >Rs.15,000. Among diabetic subjects 22(59.4%) were hypertensive whereas among non-diabetic subjects 9(51.35%) were hypertensive. The study findings revealed that, majority of the subjects with diabetes had poor sleep quality 78.4% (29), whereas among non-diabetic subjects only 51.4% (19) subjects reported poor sleep quality and the quality of sleep among non-diabetic subjects were better than diabetic subjects at (p=0.014). Conclusion: As a healthcare practitioner, the health care providers should focus their attention to the quality of sleep of their patients and should take initiative to make the people to aware about the importance of sleep in their day to day life to live healthy.